Corn intercropped with tropical grasses - Bottega, Eduardo Leonel (2017)
The intercropping corn with grasses it is a widely used practice in tropical climates, but nothing is known about its adoption in temperate regions. This study aimed to evaluate the growth influence of different grasses on corn yield due to the seeding system adopted in intercropping. The experiment was established in a 3x3 factorial scheme, the factors being composed of 3 grass seeding systems and 3 cultivars of grass. The means were evaluated by Tukey test at 5% probability. The higher amount of total dry matter was obtained by Urochloa ruziziensis cv. Ruziziensis grass. The corn intercropped with the grasses did not affect the crop yield, regardless of seeding and grass used system.